Dose exposure to the population of Lunints and Mikashevichi due to radon in residential air - Sasnouski, Alexey V.; Avetisov, Aram R.; Lukashevich, Janna A.; Vasileuski, Leu L.; Hakimov, Dilshod A.; Kirievich, Irina K. (Journal of the Belarusian State University. Ecology, 2022)
This article contains information about the levels of radon in the air of residential premises in the settlements of Luninets and Mikashevichi and their environs (Brest region, Republic of Belarus), as well as doses to the population of these territories, formed by the inhalation intake of this radioactive noble gas. The study of the integral weighted average value of the volumetric activity of radon in the air of residential premises was carried out by the track method using integrated radon track radiometers based on an accredited laboratory. Based on data on the content of radon in the air of residential premises, doses were calculated for the population of Luninets and Mikashevichi, and an analysis was made of factors that could affect the magnitude of this dose (features of building materials of residential premises, household communications, location of the house). Exposure doses to the population due to radon in the air of residential premises fell in the range from 0.9 to 7.7 mSv/year with a non-normal distribution. In the course of the study, it was found that the type of dwelling has the most significant effect on the level of radon in the air of residential premises: doses for the population living in private residential buildings with brick walls are significantly higher compared to similar doses for the population living on the first floors apartment buildings. A comparison was made of the levels of radon in the air of residential premises and doses for the population of Luninets and Mikashevichi. The levels of radon in the air of residential premises of Luninets are significantly higher than those in Mikashevichi, which refutes the impact of granite mining on the level of radon in the air of residential premises of this settlement. The calculation of lifelong oncological risks for the population of Luninets and Mikashevichi was made. When calculating 0.6*10-5 for each Bq/m3, the soncological risks fell within the range from 0.00009 to 0.00074. Based on the measurement results, maps were created that clearly demonstrate the distribution of radon levels in the air of residential premises of the studied settlements and their environs.
Keywords: radon; radiation dose; cancer risk